ANALISIS PENGARUH MOTIVASI, KOMUNIKASI, DAN KOMITMEN ORGANISASI TERHADAP KEPUASAN KERJA PEGAWAI KANTOR CAMAT TOMPOBULU KABUPATEN GOWA - Ali Baba (AkMen JURNAL ILMIAH, 2016)
Ali Baba, "Influence of Motivation, Communication and Organizational Commitment Employee Job Satisfaction In Tompobulu Gowa District Office. To know and analyze the Influence Motivation, Communication and Organizational Commitment Employee Job Satisfaction In Tompobulu Gowa District Head Office and as for the benefit of the results of this study can be used as a source of information to increase knowledge and as an additional reference materials for scientific research to be done next. Data used in this study are primary data that responses to questionnaires from respondents with data analysis using multiple linear regression with SPSS 20. The samples in this study were 30 respondents employee Tompobulu Gowa District Head Office. Results of this study stated that based on the analysis of data on a show that showed that 0608 or 60.8% of employee satisfaction is influenced by motivation, communication and organizational commitment means that 39.2% (100% - 60.8%) affected job satisfaction by other factors.